Beyond Money : Does Migration Experience Transfer Gender Norms? Empirical Evidence from Kerala, India - Joseph, George; Wang, Qiao; Chellaraj, Gnanaraj; Tas, Emcet Oktay; Andres, Luis Alberto; Javaid, Syed Usman; Rajan, Irudaya (Washington, DC: World Bank, 2022)
This paper examines the impact of return migration from Saudi Arabia and the Gulf on the transfer of gender norms to the Indian state of Kerala. Migration to countries in the Middle East has led to significant remittance flows and economic prosperity, although the effects on social norms and attitudes remain largely unexplored. The paper finds that returning migrants from Saudi Arabia tend to exhibit conservative values regarding gender-based violence and extreme attitudes pertaining to the perpetration of physical violence against women. Compared with those who have no migration experience, the attitudes of returning migrants from Saudi Arabia toward gender-based violence were more conservative by three standard deviations, while the attitudes of those returning from the Gulf were less conservative by 0.5 standard deviation. Similarly, compared with those with no migration experience, returning migrants from Saudi Arabia were more conservative by 2.6 standard deviations regarding extreme attitudes related to gender norms, such as sexual assault, while those returning from the Gulf were less conservative by 0.7 standard deviation. These results show that migration experience can have a substantial impact on the gender attitudes of returning migrants, with potential implications for migration and gender policies in Kerala and for countries that send a large share of temporary migrants overseas for work.